Alkenylazaarenes as dipolarophiles in 1, 3-dipolar cycloaddition of nitrones: regioselectivity-switchable and highly diastereoselective synthesis of multisubstituted isoxazolidines. Issue 20 (12th September 2018) - Tong, Mengchao; Zhang, Yong; Qin, Cong; Fu, Yiwei; Liu, Yonghai; Li, Hao; Wang, Wei
Abstract : Metal free 1, 3-dipolar cycloaddition between alkenylazaarenes and nitrones has been developed for the synthesis of 4-substituted isoxazolidines and 5-substituted isoxazolidines in good yields and selectivities. Abstract : Alkenylazaarenes as a novel class of dipolarophiles for 1, 3-dipolar cycloaddition (1, 3-DC) with nitrones was reported. A regioselectivity-switchable synthesis of multisubstituted isoxazolidines had been developed. In the presence of TMSOTf as catalyst, 4-substituted isoxazolidines were obtained as major products with high regio- and diastereoselectivities. Nonetheless, under microwave irradiation in a sealed system with water as solvent, exclusive 5-substituted isoxazolidines were produced in good yields.